The Influence of Foreign Investment, Information and Communication Technology, Human Resources, and Spatial Dependence on Productivity Convergence - Yusman Syahrir Ando; Doddy Aditya Iskandar (Univiversitas Dr. Djar Wattiheluw, 2024)
The structural characteristics in the Eastern Indonesia Region, such as human capital, demographics, unemployment rates, and government policies, lead to regional polarization with varying growth levels. This study examines the influence of foreign investment, information and communication technology, human resources, and spatial dependence on productivity and its convergence from 2015 to 2022 using the Spatial Durbin Model. The findings show productivity divergence, with foreign investment positively impacting TFP divergence, while ICT and human resources do not affect TFP between regions. Spatially, foreign investment and ICT positively impact TFP, whereas human resources negatively impact TFP, influencing both the region and its neighbors.